Albania Local Finance Policy Note : Programmatic Public Expenditure and Institutional Review - World Bank (Washington, DC, 2014)
Albania has undertaken major reforms in its system of local government finance since 2000. What had been a system in which local functions were ambiguous and financing was largely provided through tightly controlled earmarked grants is now one in which functions are relatively clear and local governments have more autonomy over the allocation of funds. A new system of competitive grants for infrastructure investment has been introduced. Parliament has enacted a new law on local borrowing. Within this framework, however, several controversies remain which are addressed in this policy note. In the long term Albania must also grapple with certain organizational issues. One is the role of regional governments, which now lack any major clearly defined function. While the Government's decentralization strategy proposes a range of possible functions for regional governments, most of these roles could be carried out through other means. The other organizational issue is the consolidation of small communes. The Government's decentralization strategy proposes the eventual consolidation of small local governments into larger units. International experience, however, suggests that the efficiency gains of consolidation are limited and may not be sufficient to justify the political costs of doing so. Efforts to consolidate local governments should consider alternative solutions such as inter-municipal agreements and joint service companies before proceeding.